Współczesne teorie wychowania literackiego w Czechosłowacji (tendencje, problemy, perspektywy) = Modern Theories on Literary Education in Czechoslovakia - Posledni, Petr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author treats of tendencies, problems and perspectives of development of modern theories on literary education in Czechoslovakia. He shows this development to be actuated by two factors: Expansion of the area of performance of the literary education's system and taking better advantage of the achievements of general didactics, literary science, aesthetics and psychology.
Keywords: dydaktyka literatury; Czechosłowacja - 20 w.